Further Exploration of Personal and Social Functioning: The Role of Interpersonal Violence, Service Engagement, and Social Network. Issue 10 (October 2019) - Talevi, Dalila; Pacitti, Francesca; Costa, Manuela; Rossi, Alessandro; Collazzoni, Alberto; Crescini, Claudio; Rossi, Rodolfo
Abstract : Abstract: Social functioning (SF) has mainly been studied in major psychoses in relation to symptom severity, but other factors may interfere with the achievement of a functional remission. The aim of this study is to explore interpersonal violence (IV), service engagement (SE), and social network (SN), together with demographics, as predictors of SF in a sample of subjects with severe mental illness (SMI). Consecutive adult inpatients were evaluated using self-report and clinician-rated questionnaires. Findings suggest that IV, SE, SN, male sex, and illness duration explained 39.1% of SF variance in people affected by SMI. IV was the strongest predictor, followed by sex and duration of illness. Lifetime expression of violence is a stronger predictor than lifetime exposure to violence. Positive SE and SN were found to predict SF, whereas age was not associated. This study underlines the need of other non-symptom-related variables for the comprehension of SF in mental disorders.